A Review on Impact of Health-Related Outreach Programs in Improving Quality of Life - Pallavi Singh,; Preeti Jaiswal; Akanksha Dubey; Mahima Jain; Ramswaroop Patel; Deeksha Singh (The Bioscan, 2025)
Introduction: Outreach programs have become essential in addressing healthcare disparities and improving the quality of life, particularly among vulnerable and underserved populations. Aims and Objectives: The aim of this review is to assess the effectiveness of health-related outreach programs in enhancing quality of life across different population groups. Materials and Methods: A literature search has been selected by 2 review authors independently in 3 different databases like PubMed, Scopus, Google Scholars for articles published from 2013–2024. Classification of Health Outreach Programs: An outreach program is complete entanglement between the community and health institutions or organizations. Results: From a total of 18 papers from different databases, 13 papers fulfilled the inclusion criteria. Discussion: Outreach programs play a transformative role in extending healthcare access and improving health outcomes for marginalized and underserved communities. Conclusion: In conclusion, outreach programs are not just temporary solutions; they are sustainable, impactful tools for transforming health systems and improving the quality of life for all, especially the most vulnerable.